PENGEMBANGAN WISATA HALAL UNTUK KESEJAHTERAAN MASYARAKAT DI KOTA MATARAM - Mutiaralinda Sartika Nasution; Basuki Prayitno; Ihsan Rois (istinbath, 2020)
West Nusa Tenggara (NTB) is one of Indonesia’s leading halal tourist destinations. This makes business opportunities open for the local community and will be able to improve the welfare of the community. All districts participated in the development of halal tourism to increase the number of tourist visits to NTB. The city of Mataram, the capital of the NTB province, is no exception. Mataram is also actively building and developing halal tourism by packaging existing tourist destinations into attractive halal tourist destinations. Seeing the rapid development of halal tourism in NTB, this study was conducted to examine the development of Halal Tourism in the City of Mataram and to determine the contribution of the development of halal tourism to the welfare of the people in Mataram City. This research is a descriptive qualitative study in which the primary data are informants from the City of Mataram Tourism Office, Mataram City Promotion Board, Tourism Actors and tourists that visiting Mataram while secondary data are obtained from various reports, books, publications, websites and others. The results of this study aimed that the development of halal tourism carried out by the Mataram City Government was quite good. This is proven by the increasing number of tourists visiting Mataram City each year. Development of halal tourism is done by improving facilities and infrastructure at tourist destinations, promoting both local and international, providing public transportation that is good enough to access tourist attractions, providing accommodations in accordance with sharia provisions so as to provide comfort for tourists especially Muslim tourists. With various efforts to develop tourist destinations that have been carried out by the Government of the City of Mataram has an impact on improving the welfare of the people of the City of Mataram, which is illustrated through the increase in the HDI index from year to year.